1999
DOI: 10.1007/bf01279093
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida

Abstract: Summary. During Petunia hybrida seed development, the MADSbox genes encoding the floral binding proteins (FBP) 7 and 11 are expressed in the seed coat and not in the endosperm or embryo. These proteins are thought to function as transcription factors and are essential for ovule formation in Petunia spp. Immunocytochemical methods were used to analyze the distribution of FBP7 and FBPll after fertilization in wild type and ectopic and cosuppression mutants. During the first nine days of seed development the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Recently, Wittich et al analysed the post fertilization development of Petunia seeds and demonstrated that FBP7/11 proteins are present in the cell nuclei. This nuclear position is in agreement with their supposed role as transcription factors (Wittich et al, 1999 [18] ).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recently, Wittich et al analysed the post fertilization development of Petunia seeds and demonstrated that FBP7/11 proteins are present in the cell nuclei. This nuclear position is in agreement with their supposed role as transcription factors (Wittich et al, 1999 [18] ).…”
Section: Introductionsupporting
confidence: 85%
“…In addition, parts of sepals with ovule-like structures were dissected out. Further processing was as described by Wittich et al (1999 [18] ). In short, samples were rapidly freezefixed in liquid propane, the frozen samples were freeze-substituted in acetone containing 1 % glutaradehyde in a freeze-substitution machine, further dehydrated through an acetone± ethanol series, and infiltrated and embedded in butyl methyl methacrylate (BMM).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Seeds prepared for visualization of microtubules were cryo‐fixed, freeze‐substituted, and embedded in butyl methyl methacrylate (Wittich et al ., 1999). Sections 2–3 ”m in thickness were washed in acetone, blocked, and labeled with monoclonal anti‐α‐tubulin (1 : 100, Sigma) and goat antimouse antibody (GaM‐IgG) conjugated to Alexa 488 (1 : 200, Molecular Probes, Leiden, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…After three washes with water, the sections were incubated in 4% sodium sulfite at room temperature for 5 min, mounted in 50% glycerol, and photographed using a Nikon (Tokyo, Japan) Eclipse 400 fluorescence microscope. Segments ‫1ف(‬ mm thick) from the same internodes used for histochemical analysis were used for immunolocalization on the basis of the protocol of Wittich et al (1999) with modifications. The segments were fixed in 4% paraformaldehyde in 0.1 M PBS (4 mM sodium phosphate, pH 7.4, and 200 mM NaCl) for 12 hr at 4ЊC.…”
Section: Histochemical Lignin Analysis Immunolocalization and Micromentioning
confidence: 99%